The global proportion and volume of unrecorded alcohol in 2015. - Probst, Charlotte; Fleischmann, Alexandra; Gmel, Gerhard; Poznyak, Vladimir; Rekve, Dag; Riley, Leanne; Rylett, Margaret; Shield, Kevin D.; Rehm, Jürgen (Journal of Global Health, 2019)
Background: Alcohol consumption is associated with elevated risks of disease and injury, and the best indicator of the level of consumption in a country is total alcohol per capita (APC) consumption among adults which comprises recorded consumption and unrecorded consumption. While recorded consumption can be assessed with small measurement bias via taxation or other governmental records, unrecorded consumption is more difficult to assess. The objectives of this study were to estimate the country-specific proportion and volume of unrecorded APC in 2015, to identify main sources of unrecorded alcohol and to assess to what extent experts perceive unrecorded alcohol as a public health, social, and financial problem.Methods: Estimates of unrecorded APC were based on a multilevel fractional response regression model using data from World Health Organization's (WHO) STEPwise approach to surveillance surveys (16 countries, 66 188 participants), estimates from the routine WHO reporting on key indicators of alcohol use (189 countries), and a nominal group expert assessment (42 countries, 129 experts). Expert assessments also included data on the sources of unrecorded alcohol and the perception of unrecorded alcohol as a public health, social, and financial problem.Results: The volume of global unrecorded APC was 1.6 L pure alcohol, representing 25% of the total APC. The volume of unrecorded APC was highest in Europe (2.1 L per capita), while the proportion of unrecorded APC was highest in the WHO Eastern Mediterranean region (57% of the total alcohol). In countries with available data, homemade alcohol was identified as a major source of unrecorded alcohol. The majority of experts considered unrecorded alcohol to be a public health (62%), social (60%), and financial problem (54%).Conclusions: High volumes of unrecorded alcohol are consumed globally; however, the volumes consumed and the sources of the unrecorded alcohol exhibit large geographical variation.